Digital Competence of Post-Pandemic Teachers Based on Gender, Work Period, and Certification Factors - Saluky Saluky; Onwardono Rit Riyanto; Siti Rahmah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Technological developments must be balanced with the skills of mastering these technological products. Digital competence is highly correlated with the use and awareness of teachers in applying technology to their professional activities. This article presents diagnostic results on Teachers' self-perceptions of their digital competence. The digital competency framework based on DigiComp has five dimensions as an evaluation tool. The sample of this study consisted of 11 upper-middle-level teachers with various characteristics. Questionnaires were used to collect teacher response data. Descriptive analysis is used to diagnose teacher competence. The results showed that teachers have good skills in the aspects of information and data literacy as well as communication and collaboration. Digital content creation and problem solving skills related to the use of technology still need improvement efforts through improving soft skills. Increasing digital competency skills really needs to be pursued to integrate technology into the learning process